Are Empty-Nest Elders Unhappy? Re-examining Chinese Empty-Nest Elders’ Subjective Well-Being Considering Social Changes - Zhang, Yan (Frontiers in Psychology, 2020)
Aging, the one-child policy, and migration have altered Chinese family structure and the number of empty-nest elders is increasing. Since living without children runs in the opposite direction of filial piety, empty-nest elders have typically been negatively viewed and depicted as unhappy. However, individualization and the unbalanced development of China may decrease the impact of children but increase the impact of the spouse and rural-urban gaps on elders’ well-being. Therefore, this study re-examined the subjective well-being of empty-nest elders considering these social changes. Participants (N = 765; age range = 60–94 years, Mage = 70.25 years, SDage = 7.85; men = 45%) were recruited from two large cities, two small cities, and two rural areas in China. Elders’ subjective well-being was measured by the Memorial University of Newfoundland Scale of Happiness–Chinese version. Results showed that participants were happy on average; empty-nest elders were not unhappier than non-empty-nest elders. Elders living without a spouse and rural elders had high risks of being unhappy. Policymakers should thus shift their attention from empty-nest families to the widowed and rural elders.